2017
DOI: 10.1002/ejic.201700098
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Trichlorostannyl Ligand in Tin–Ruthenium Arene Complexes: Experimental and Computational Studies

Abstract: A set of neutral and ionic ruthenium arene trichlorostannyl complexes are reported herein. The tin(II) compounds L 1 SnCl {1; L 1 = [2-(CH 2 NEt 2 )-4,6-(tBu) 2 C 6 H 2 ] -} and [L 2 SnCl][SnCl 3 ] {2; L 2 = 2,6-[(CH 3 )C=N(C 6 H 3 -2,6-iPr 2 ) 2 ]C 5 H 3 N} showed a rather different reactivity towards the ruthenium complex [(η 6cymene)RuCl] 2 (η-Cl) 2 . As a consequence, the neutral complex [Ru(η 6 -cymene)(L 1 SnCl)Cl 2 ] (4) and the ionic compound [L 2 SnCl][Ru(η 6 -cymene)(SnCl 3 ) 2 Cl] (8) were isolated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…No over oxidations of tested benzyl amines were detected. The high catalytic activity of 3 maybe attributed to least negative charge on the central Ru atom (−0.34e) in comparison with others tested compounds. Since the efficient complex 3 contains donating ligand L 2 PPh 2 , where L 2 is amino‐phosphine with the PN H moiety, complex 3 has been efficiently anchored to silica gel via N H hydrogen bonding and heterogeneous catalyst 3 ‐ silica was prepared.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…No over oxidations of tested benzyl amines were detected. The high catalytic activity of 3 maybe attributed to least negative charge on the central Ru atom (−0.34e) in comparison with others tested compounds. Since the efficient complex 3 contains donating ligand L 2 PPh 2 , where L 2 is amino‐phosphine with the PN H moiety, complex 3 has been efficiently anchored to silica gel via N H hydrogen bonding and heterogeneous catalyst 3 ‐ silica was prepared.…”
Section: Discussionmentioning
confidence: 81%
“…The compounds 1 , 3 and 5 were very active under these conditions, while complexes containing SnCl 3 ligand were less effective (Table ). Our previous study showed that the SnCl 3 group increased negative charge on the ruthenium atom (range of −0.78 to −1.02 e ) in comparison with Cl atom (the charge on the ruthenium −0.34 to −0.55 e ) . This indicates that negative charge on the Ru atom decrease the catalytic activity of the catalyst.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The reaction of half-sandwich ruthenium(II) arene complexes [(η 6 -C 6 H 6 )RuCl 2 (PR 3 )] (R = aryl or O-Aryl, O-alkyl) with SnCl 2 is also known to yield a Ru(II) complex exhibiting a strong covalent Ru-Sn bond via facile insertion of the SnCl 2 moiety into the Ru-Cl bond [35,36]. While the reaction of SnX 2 (X = halide) with other metals, such as palladium and platinum, has been extensively studied [37,38], the analogous reaction with ruthenium derivatives has received far less attention.…”
Section: Chart 1 Examples Of Anti-cancer Ruthenium-based Agentsmentioning
confidence: 99%